Role of Dividend Policy in Determining the Market Value of Share Companies in Nigeria Stock Exchange - Kayode Oluwafemi Ishola; Timothy Aondona Aondover (Britain International for Academic Research (BIAR) Publisher, 2026)
This study examines the role of dividend policy in determining the market value of shares companies in Nigerian Stock Exchange. Dividend policy remains an important corporate financial decision because it determines the proportion of corporate earnings distributed to shareholders and the amount retained for future investment and business expansion. The study is anchored on Fundamentalist Theory, which emphasises the use of firms' financial and economic indicators, including earnings and dividend records, in assessing the intrinsic value and future performance of securities. The study adopts a qualitative research approach based on secondary data obtained from relevant published literature, including scholarly journal articles, books, corporate financial reports, and available records on dividend policy and share price performance. The secondary data were reviewed and thematically analysed to establish the relationship between dividend policy and the market value of shares. The review indicates that dividend per share, dividend yield and dividend payout ratio are important indicators associated with investors' perceptions and share price movements, although empirical findings remain mixed across firms and markets. The study further highlights the continuing debate between the dividend irrelevance perspective of Modigliani and Miller and the dividend relevance arguments advanced by scholars such as Gordon and Walter. It concludes that dividend policy remains a significant consideration in investors' assessment of listed companies and may influence the market value of shares, particularly in an imperfect capital market such as Nigeria.